2021
DOI: 10.1039/d0nj05930g
|View full text |Cite
|
Sign up to set email alerts
|

Eu(iii)-Doped tri-calcium Ca3(1−X−Z)MZ(PO4)2AX:X host array: optical investigations of down-conversion red phosphor for boosting display intensity and high color purity

Abstract: Eu3+-activated double and triple phosphates were synthesized by the high temperature solid-state reaction. These phosphors were characterized by X-ray diffraction (XRD), SEM (Scanning electron microscopy), Fourier transform infrared spectroscopy (FT-IR)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…These peaks were due to 7 F 0 → 5 L 6 , 7 F 0 → 5 D 2 , and 7 F 0 → 5 D 1 transitions and demonstrated that UV, blue, green laser, and light‐emitting diodes were proficient exciting sources that acquired Eu 3+ emission. [ 43,48 ] Detailed analysis for the emission of Eu 3+ was carried out for each of the excitation wavelength to confirm the effect of the pumping wavelength on the emission spectra. Figure 11(a), (b), and (c) shows the PL emission spectra of the YZO phosphor at 395 nm, 466 nm and 534 nm, respectively, with a correspondingly dominant peak at 618 nm.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks were due to 7 F 0 → 5 L 6 , 7 F 0 → 5 D 2 , and 7 F 0 → 5 D 1 transitions and demonstrated that UV, blue, green laser, and light‐emitting diodes were proficient exciting sources that acquired Eu 3+ emission. [ 43,48 ] Detailed analysis for the emission of Eu 3+ was carried out for each of the excitation wavelength to confirm the effect of the pumping wavelength on the emission spectra. Figure 11(a), (b), and (c) shows the PL emission spectra of the YZO phosphor at 395 nm, 466 nm and 534 nm, respectively, with a correspondingly dominant peak at 618 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The highest intensity was obtained at 1.0 mol% concentration for the Sm 3+ ‐doped Ca 8.25 Na 1.5 Al 6 O 18 phosphor and this then decreased in the yellowish‐red region on excitation at 346 nm, as shown in the chromaticity diagram. The colour purity of the prepared Sm 3+ ‐doped Ca 8.25 Na 1.5 Al 6 O 18 phosphor sample was calculated using the relationship [ 30‐33 ] :…”
Section: Resultsmentioning
confidence: 99%
“…The predictable fleecy morphology of the particles is usually obtained from simple combustion synthesis and the voids are caused by the vast gaseous matter that runs away due to extraordinary exothermicity. [ 28,29 ] The given morphology revealed that the phosphor might be a potential candidate for WLEDs and display devices. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%